Dietary Polyphenols, Resveratrol and Pterostilbene Exhibit Antitumor Activity on an HPV E6-Positive Cervical Cancer Model: An in vitro and in vivo Analysis - Chatterjee, Kaushiki; Mukherjee, Sumit; Vanmanen, Jonathan; Banerjee, Probal; Fata, Jimmie E. (Frontiers in Oncology, 2019)
Human papilloma virus (HPV)-induced cervical cancer is one of the most frequent cancers in women residing in underdeveloped countries. Natural compounds like polyphenols continue to be of scientific interest as non-toxic effective alternative treatments. Our previous work showed the efficacy of two polyphenols, resveratrol and pterostilbene on human HeLa cells. Here we explored the in vitro anti-cancer activity and in vivo anti-tumor potential of these two structurally similar compounds on HPV oncogene E6 and E7 positive murine TC1 cells. In vitro analysis confirmed the cytotoxic potential of both resveratrol and pterostilbene compounds with each having a low IC50 value and each showing the ability to downregulate viral oncogene E6. Further in vivo studies on TC1 tumors developing in mice indicated that treatment with either resveratrol or pterostilbene can significantly inhibit tumor development, with both compounds capable of downregulating E6 and VEGF tumor protein levels. Interestingly, the decrease in tumor size in pterostilbene was associated with tumor cell apoptosis, as indicated by an upregulation of activated caspase-3 whereas in resveratrol-treated mice it was accompanied by arrest of cell cycle, as indicated by a downregulation of PCNA. Thus, resveratrol and pterostilbene can serve as potential antineoplastic agents against HPV E6+ tumors and may suppress tumor growth via two different mechanisms.